2010
DOI: 10.3109/01676830903207828
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Primary Acquired Nasolacrimal Duct Obstruction

Abstract: This study did not find any evidence in favor of the role of viral infection (HSV1, HSV2, HPV), eye make-up, and sex hormones in pathogenesis of PANDO. No abnormal pathology was found in lacrimal sac biopsy of patients with PANDO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…A non-specific chronic inflammation with fibrosis is the most commonly reported histopathological finding in lacrimal sac wall biopsy specimens obtained during DCR [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. However, many other pathological processes (of special importance are those with malignant biological behavior) may arise in the lacrimal sac and masquerade as chronic inflammation with clinical symptoms and signs of presumed primary chronic dacryocystitis [1,3,.…”
Section: Introductionmentioning
confidence: 99%
“…A non-specific chronic inflammation with fibrosis is the most commonly reported histopathological finding in lacrimal sac wall biopsy specimens obtained during DCR [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. However, many other pathological processes (of special importance are those with malignant biological behavior) may arise in the lacrimal sac and masquerade as chronic inflammation with clinical symptoms and signs of presumed primary chronic dacryocystitis [1,3,.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic chronic inflammation, with or without fibrosis, occurs in clinically presumed primary acquired nasolacrimal duct obstruction (PANDO) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. A wide variety of causes, such as specific inflammatory [9][10][11][12][13], traumatic, mechanical, or neoplastic [14][15][16][17][18] may mimic idiopathic inflammation [19][20][21] in secondary acquired lacrimal drainage system obstruction (SALDO). Neoplastic causes are of special clinical interest ( Figure 1) [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…It affects women, typically after age 40, more frequently than men (Woog, 2007). Studies have shown the higher incidence of NLDO in women is not related to sexual hormones, viral infection, or eye make-up (Kashkouli et al, 2010). The increased incidence is believed to be related to the anatomical difference between the bony nasolacrimal excretory system in men versus women (Groessl et al, 1997).…”
mentioning
confidence: 98%